Euphorbia tirucalli modulates gene expression in larynx squamous cell carcinoma - Franco-Salla, Gabriela Bueno [UNESP] (2016)
Background: Some plants had been used in the treatment of cancer and one of these has attracted scientific interest, the Euphorbia tirucalli (E. tirucalli), used in the treatment of asthma, ulcers, warts has active components with activities scientifically proven as antimutagenic, anti-inflammatory and anticancer. Methods: We evaluate the influence of the antitumoral fraction of the E. tirucalli latex in the larynx squamous cell carcinoma (Hep-2), on the morphology, cell proliferation and gene expression. The Hep-2 cells were cultivated in complete medium (MEM 10%) and treated with E.tirucalli latex for 1, 3 ,5 and 7days. After statistically analyzing the proliferation of the tested cells, the cells were cultivated again for RNA extraction and the Rapid Subtractive Hybridization (RaSH) technique was used to identify genes with altered expression. The genes found using the RaSH technique were analyzed by Gene Ontology (GO) using Ingenuity Systems. Results: The five genes found to have differential expression were validated by real-time quantitative PCR. Though treatment with E. tirucalli latex did not change the cell morphology in comparison to control samples, but the cell growth was significantly decreased. The RaSH showed change in the expression of some genes, including ANXA1, TCEA1, NGFRAP1, ITPR1 and CD55, which are associated with inflammatory response, transcriptional regulation, apoptosis, calcium ion transport regulation and complement system, respectively. The E. tirucalli latex treatment down-regulated ITPR1 and up-regulated ANXA1 and CD55 genes, and was validated by real-time quantitative PCR. Conclusions: The data indicate the involvement of E. tirucalli latex in the altered expression of genes involved in tumorigenic processes, which could potentially be applied as a therapeutic indicator of larynx cancer.